2021
DOI: 10.1039/d0fo02236e
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on separation of selenoproteins/Se-enriched peptides and their physiological activities

Abstract: Extracting Se-enriched proteins and peptides from Se-enriched agricultural products is crucial for improving the nutritional status of Se in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 120 publications
0
26
0
Order By: Relevance
“…Nevertheless, selenium is considered both beneficial and toxic depending on its form and amount ingested ( 7 ). The organic form of selenium is superior to the inorganic form in terms of bioavailability and toxicity for meeting human dietary requirements ( 8 ). Consequently, it is necessary to explore new selenium carriers to address the potential problems associated with selenium deficiency and selenium toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, selenium is considered both beneficial and toxic depending on its form and amount ingested ( 7 ). The organic form of selenium is superior to the inorganic form in terms of bioavailability and toxicity for meeting human dietary requirements ( 8 ). Consequently, it is necessary to explore new selenium carriers to address the potential problems associated with selenium deficiency and selenium toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…19 Selenium (Se) is acknowledged as a microelement considered vital for health, mainly due to its anti-inflammatory and antioxidant functions. 20 Research has shown that Se treatment can protect the lungs of rats from the acute injury induced by allergies, sepsis, and various agricultural chemicals, such as paraquat and dimethoate, by activating GSH-Px, attenuating oxidants, and reducing the inflammatory response and lipid peroxidation. [21][22][23] In humans, selenocysteine is found at the active centers of 25 selenoproteins responsible for the nutritional function of Se.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, integrating the antioxidant and anti-inflammatory properties of Se and peptides has diversified their application prospects. 20,24,25 Previous studies have shown that Se-containing soybean peptides exhibited excellent antioxidant and immunoregulation capacity. 26,27 This study established a mouse model involving lung injury via the nasal inhalation of PM2.5 to understand the underlying mechanisms of PM2.5-induced lung toxicity and the protective effect of Se-SPep.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that Se, as an essential micronutrient with antioxidant properties, can improve immune functions in the body by regulating humoral immunity, cellular immunity, and nonspecific immunity (Carlson et al., 2010 ; Esmail et al., 2020 ). Se plays an essential physiological role in the body in the form of selenoprotein (Zhang et al., 2021 ). When dietary Se intake is insufficient, the selenoprotein content in the body tissues is significantly reduced, inhibiting the growth and development of immune cells.…”
Section: Introductionmentioning
confidence: 99%